A phonic Braille recognition system based on a self-powered sensor with self-healing ability, temperature resistance, and stretchability. Issue 10 (9th August 2022) - Dai, Xingyi; Huang, Long-Biao; Sun, Zhenhua; Du, Yuzhang; Xue, Boen; Wong, Man-Chung; Han, Jiancheng; Liang, Qihua; Wu, Yongpeng; Dong, Biqin; Kong, Jie; Hao, Jianhua
Abstract : A Braille recognition system with phonic functionality has been developed using self-powered sensor. The electrical signals generated by the sensor can be recorded and converted into audio form, thus it can be decoded and read out in real-time. Abstract : Braille recognition is of great significance for the visually impaired and blind people to achieve convenient communication and learning. A self-powered Braille recognition sensing system with long-term survivability and phonic function could provide those people with greatly enhanced access to information and thus improve their living quality. Herein, we develop a skin-like self-powered Braille recognition sensor with self-healing, temperature-resistant and stretchable properties, which is further connected with the designed audio system to realize real-time conversion from mechanical stimulus to electrical signals and then to audio signals. The sensor is fabricated using dynamic interaction-based self-healing materials, which constitute an imine bond-based cross-linked polymer for the triboelectric layer and a hydrogen bond-based organohydrogel for the electrode layer. Moreover, the conductive organohydrogel-based electrode is provided with stretchable, anti-freezing, and non-drying properties. Consequently, minimized impact on the output performance of the sensor is found under mechanical impact, harsh environments and large deformation, enabling a long lifespan, high durability, and good stability. The self-powered sensor can be applied in a Braille recognition system, in which the Braille characters can be further decoded and read out. This work shows a reliable and flexible device with promising prospects in information technology.